Training On Making Liquid Organic Fertilizer (Poc) For Entrepreneur Cadres In Banda Aceh - Alkautsar, Alkautsar; Yaman, M. Aman; Fuadi, Zahrul; Mulyadi, Mulyadi; Makmur, Ali; Mudatsir, Mudatsir; Yustendi, Dedhi; Siagian, Afwandy Taga; Hibran, Syukron (Departemen of Animal Science, Agriculture Faculty, Syiah Kuala University, 2024)
Training Program on Liquid Organic Fertilizer Production for Entrepreneur Cadres consisting of 20 members. The training aims to enhance the community's knowledge and skills in utilizing waste materials to produce organic fertilizer, as well as reducing dependency on chemical fertilizers. The training begins with the opening ceremony by the MC and delivery of materials, followed by the main activity of liquid organic fertilizer production training using compost as the main ingredient. Then, theoretical materials on the production of liquid organic fertilizer are provided. Subsequently, practical sessions or demonstrations on liquid organic fertilizer production are conducted. Participants are given opportunities for discussion and questions during the training process. This study provides valuable insights to support the management and development of Liquid Organic Fertilizer in Banda Aceh.